Cigarette smoking and associated health risks among students at five universities - Halperin, Abigail C. (Oxford University Press, 2010)
INTRODUCTION: While most college students and other young adults who smoke fall into the light and intermittent smoking (LITS) category, they remain at risk for tobacco dependence and other adverse health effects from their smoking. This study examines smoking patterns, tobacco dependence, and other health variables among students at five universities to better understand how to identify and address tobacco use and related risks in a college health clinic setting. METHODS: A health screening survey was completed by 2,091 college and graduate student volunteers seeking routine care at their university health centers or participating in a health class. Independent health variables were analyzed descriptively and in regression analyses with three levels of smoking (none, non-daily, and daily) and tobacco dependence to determine predictors and associated risks. RESULTS: Nearly a quarter of students reported any current smoking, 41% of whom reported smoking less than 1 cigarette/day (cpd). Of the daily smokers, 80% smoked less than 10 cpd but 45% met criteria for tobacco dependence. Any smoking was associated with high-risk alcohol use, risky driving, relational abuse, depression, less exercise, and utilization of emergency and mental health services. In regression analyses, students who experienced depression had more than double the odds of being dependent smokers (odds ratio [OR] = 2.32), as did those who reported abuse (OR = 2.07) or sought mental health counseling (OR = 2.09). DISCUSSION: Student health providers should be alerted to the multiple risks and comorbidities that occur among all smokers, including LITS, and intervene concurrently to help prevent or mitigate adverse outcomes that result from these conditions and behaviors.